2019
DOI: 10.1155/2019/5028534
|View full text |Cite
|
Sign up to set email alerts
|

Is It T3 Thyrotoxicosis? A Case of Falsely Elevated Tri-Iodothyronine (T3) Levels Leading to a Diagnosis of Multiple Myeloma

Abstract: We are presenting a case of falsely elevated T3 levels in a patient due to interference from monoclonal immunoglobulins. A 56-year-old, clinically euthyroid man referred to the endocrinology clinic of the Aga Khan university, Karachi Pakistan, for possible T3 thyrotoxicosis after thyroid function tests revealed total T3 >12.32 nmol/L (reference range 0.6–2.79), normal TSH, and total T4 level. There was a mismatch in clinical and laboratory parameters and preliminary laboratory results were suggestive of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“… 44 In contrast to publication by, 41 the mean level of fT3 observed in the malaria cases was above the normal Ghanaian level of 2.73–4.13 pmol/L. 45 In isolated fT3 thyrotoxicosis, fatigue, lethargy, and weight loss have been reported, 46 clinical presentations that are commonly observed in about 74% of children with malaria. 5 However, it is not clear whether these symptoms observed in malaria cases could be attributed to elevated fT3.…”
Section: Discussionmentioning
confidence: 78%
“… 44 In contrast to publication by, 41 the mean level of fT3 observed in the malaria cases was above the normal Ghanaian level of 2.73–4.13 pmol/L. 45 In isolated fT3 thyrotoxicosis, fatigue, lethargy, and weight loss have been reported, 46 clinical presentations that are commonly observed in about 74% of children with malaria. 5 However, it is not clear whether these symptoms observed in malaria cases could be attributed to elevated fT3.…”
Section: Discussionmentioning
confidence: 78%
“…Ram et al [ 5 ] reported another case of factitious isolated TT3 elevation. Here, a 56-year-old man was investigated for a TT3 reported to be extremely high at 800 ng/dL (39–181) while TT4 and free T3 (FT3) were normal.…”
Section: Discussionmentioning
confidence: 99%
“…The normal concentrations of FT3, FT4, and TSH were 2.3 to 4.2 pg/mL, 0.89 to 1.76 ng/Dl, and 0.55 to 4.78 μIU/mL, respectively, in this study. Because the total thyroid hormone in MM patients has been spuriously elevated in previous studies, [23][24][25] we did not include total T3 (TT3) and total T4 (TT4) for analyses in this study.…”
Section: Data Extraction and Laboratory Evaluationmentioning
confidence: 99%